METHODOLOGY OF PIRLS RESEARCH IN PRIMARY EDUCATION - Qurbonova Makhtuma Fazliddinovna (Web of Journals Publishing, 2023)
This article examines the ways of preparing junior schoolchildren for PIRLS assignments in literary reading lessons in primary grades. The essence of the international research PIRLS, a comparative analysis of educational systems of different countries and the exchange of experience to improve the quality of reading and understanding of the text by junior schoolchildren of Uzbekistan are revealed. The article pays attention to the importance of developing reading skills, understanding the text and the specificity of mastering this skill by students for further education in high school.
Keywords: reading skill, recoding, technical and semantic side of reading, PIRLS, analysis, international research, information search, value judgment, PIRLS structure, interactive tasks, speech development.